TANTANGAN PRODUKTIVITAS PERTANIAN: REFLEKSI KEGIATAN FOCUS GROUP DISCUSSION PROGRAM BERSINAR DI KARIKIL TASIKMALAYA - Fauziah, Marisa; Arikah, Khopipah; Hidayah, Dede Urfah; Novitasari , Nastiti (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Based on the results of Focus Group Discussion (FGD) activities, it was found that the reality that occurred was so complex agricultural development constraints, especially from the factor of active involvment of local governments with various challenges felt by local people who work as farmers and independent farming as the main subject in determining agricultural productivity and local community leaders in supporting the agricultural sector in the Karikil, Mangkubumi, Tasikmalaya. Focus Group Discussion activities of BERSINAR (Gardening and Healing with the Qur’an) were carried out in Karikil. This activity was attanded by several community leaders and local resident. The FGD activity ob sozialitazion of the BERSINAR program aims to inform the program that will be implemented as well as open a discussion forum for the community so that problems and obstacles that occur in the agricultural sector can be known. This discussion activity has founded regarding the obstacles faced; lack of government presence, people do not understand modern agricultural techniques, labor crisis (farmers), inadequate fertilizer and agricultural equipment, and farmers have never been given modern agricultural education.